2007
DOI: 10.1073/pnas.0707051104
|View full text |Cite
|
Sign up to set email alerts
|

Rapid dental development in a Middle Paleolithic Belgian Neanderthal

Abstract: The evolution of life history (pace of growth and reproduction) was crucial to ancient hominin adaptations. The study of dental development facilitates assessment of growth and development in fossil hominins with greater precision than other skeletal analyses. During tooth formation, biological rhythms manifest in enamel and dentine, creating a permanent record of growth rate and duration. Quantification of these internal and external incremental features yields developmental benchmarks, including ages at crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
180
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(188 citation statements)
references
References 34 publications
8
180
0
Order By: Relevance
“…Long-period line periodicities for most juvenile specimens were observed with 0.7-μm phase contrast scans (SI Appendix, Figs. S12 and S13), except the Scladina individual, which was physically-sectioned (13) and later confirmed with synchrotron imaging. Crown formation time estimates for the Obi Rakhmat 1 individual were used for age-at-death calculation only (detailed below).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…Long-period line periodicities for most juvenile specimens were observed with 0.7-μm phase contrast scans (SI Appendix, Figs. S12 and S13), except the Scladina individual, which was physically-sectioned (13) and later confirmed with synchrotron imaging. Crown formation time estimates for the Obi Rakhmat 1 individual were used for age-at-death calculation only (detailed below).…”
Section: Methodsmentioning
confidence: 95%
“…Studies of dental growth have revealed that Pliocene to Early Pleistocene hominin ontogeny was more rapid than that of recent humans (12,16,17), but data from limited Neanderthal samples continues to be vigorously debated (7,13,18). A paucity of information on dental development in hominins postdating Homo erectus, coupled with conflicting interpretations of Neanderthal ontogeny, complicates assessment of the modern human (fossil and recent Homo sapiens) and Neanderthal ancestral condition.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps the large-brained species of Middle Pleistocene hominins, which the Salé and SH14 specimens belong to, had already acquired most of the human pattern. However, evidence has shown that later Neandertals still had more rapid dental development than extant Homo sapiens (20).…”
mentioning
confidence: 99%